BIOCHEMICAL CONSTITUENTS OF WITHANIA SOMNIFERA UNDER THE INDOLE-3-BUTYRIC ACID AND TRIAZOLE SOIL DRENCHING TECHNIQUES - SAKTHIVEL, P.; KISHOREKUMAR, A.; SRIDHARAN, R. (Journal of Plant Stress Physiology)
The present study aimed at understanding the effect of indole-3-butyric acid (IBA) and triazole compounds viz., triadimefon (TDM) and propiconazole (PCZ) on the biochemicals of ashwagandha. Treatments were given on 50, 90 and 130 days after sowing (DAS). Biochemical constituents such as proline, glycine betaine and total alkaloids content were determined. It was observed that proline, glycine betaine and alkaloids content were enhanced by TDM and PCZ than followed by IBA treatment when compared to control for respective growth stages. Among the treatments, triazole compounds caused pronounced effect to the biochemical accumulation in higher level when compared to IBA treatment. These results suggest that, triazole active compounds act as a growth regulator also influence hormonal balance and great significance, which is helpful to satisfy the needs of enhance the biochemical contents in Ashwagandha.